The influence of face-to-face coaching and Artificial Intelligence coaching towards customer engagement among gym users / Muhammad Syazwan Maszuan and Rozita Abdul Latif - Maszuan, Muhammad Syazwan; Abdul Latif, Rozita (Universiti Teknologi MARA, Negeri Sembilan, 2025)
With the rising importance of fitness, sustaining customer engagement remains a challenge despite increasing gym attendance. This study looks at how AI makes coaching affordable and accessible while in-person coaching offers more tailored support. Face-to-face and AI coaching influence gym users’ engagement by analyzing supervision, feedback, and emotional connections. Addressing gaps in engagement and effectiveness, this research aims to enhance long-term gym commitment through innovative coaching methods. This quantitative, non-experimental study used a questionnaire survey to collect data from 112 gym customers in Melaka. Purposive sampling targeted individuals aged 18 and above who experienced both face-to-face and AI coaching. Key variables, including engagement, supervision, and feedback, were measured using structured survey questions to evaluate the impact of both coaching methods on customer engagement.